SUSTAINABILITY-LED INNOVATION (SLI) MODEL - Prabowo, Stanley; Budiono , Sunarto; Winarno , Agung; Rahayu , Wening Patmi (Neraca: Jurnal Ekonomi, Manajemen dan Akuntansi, 2025)
The article aims to examine the benefits of the Sustainability-Led Innovation Model, Sustainable Innovation & ESG (Environmental, Social, and Governance), and the role of technology in supporting innovation. Sustainability-led innovation has emerged as an essential approach to addressing global challenges related to the environment and society. This article explores how companies and organizations apply sustainability principles in their innovation processes and their impact on business performance and the achievement of sustainable development goals. Through in-depth literature analysis and case studies, it is found that sustainability-led innovation not only drives resource efficiency and reduces environmental impacts but also creates new opportunities for market differentiation and enhances corporate reputation. This article also identifies key factors that influence the successful implementation of sustainability innovation, such as management commitment, integration of social and environmental values in corporate strategy, and collaboration with external stakeholders. These findings provide valuable insights for decision-makers and practitioners in developing innovation strategies that are aligned with sustainability principles, which in turn can make positive contributions to society and the planet.